2014
DOI: 10.1186/1756-0500-7-832
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, social acceptance, and awareness of waterpipe smoking among dental university students: a cross sectional survey conducted in Jordan

Abstract: BackgroundWaterpipe tobacco smoking is increasing in popularity especially among young adults. This spread could be related to limited knowledge of the negative health effects of waterpipe smoking. In this study, prevalence, social acceptance, and awareness of waterpipe smoking were examined among dental university students.MethodsThis is a cross-sectional survey study, where a self-administered questionnaire was completed by a sample of dental university students in Jordan.ResultsStudents (n = 547) reported c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
24
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 29 publications
4
24
1
3
Order By: Relevance
“…This evidence reveals varying degrees of WTS use and popularity in different contexts, which could partially be due to existing tobacco laws and in part due to the social and cultural acceptability of WTS among youth [33, 34]. In addition, when considering the higher reported prevalence of WTS among our study sample in comparison with the prevalence in countries such as the U.S. and the U.K., it is worth pointing out that WTS has been linked to social class and prestige in the Middle Eastern culture, while the opposite was true in Western countries [8, 9, 19, 3538]. Some studies in the U.S. have also found a higher WTS prevalence among university students from Arab or Middle Eastern decent in comparison to students from other backgrounds [31, 39].…”
Section: Discussionmentioning
confidence: 80%
“…This evidence reveals varying degrees of WTS use and popularity in different contexts, which could partially be due to existing tobacco laws and in part due to the social and cultural acceptability of WTS among youth [33, 34]. In addition, when considering the higher reported prevalence of WTS among our study sample in comparison with the prevalence in countries such as the U.S. and the U.K., it is worth pointing out that WTS has been linked to social class and prestige in the Middle Eastern culture, while the opposite was true in Western countries [8, 9, 19, 3538]. Some studies in the U.S. have also found a higher WTS prevalence among university students from Arab or Middle Eastern decent in comparison to students from other backgrounds [31, 39].…”
Section: Discussionmentioning
confidence: 80%
“…The majority had used both cigarettes and waterpipe tobacco. Nearly half of the women reported that they smoked at home in the presence of their parents (26). These findings underscore the extent of the smoking problem in our population, especially among the younger age groups, and the urgent need for effective smoking cessation interventions.…”
Section: Source: King Hussein Cancer Center Registry Data (July 2006-mentioning
confidence: 61%
“…Saat ini, penggunaan shisha dalam merokok tembakau berkontribusi pada peningkatan skala besar penggunaan tembakau diseluruh dunia, kebiasaan sejak 400 tahun yang lalu dan kini datang kembali. 1,2,3 Merokok shisha menjadi populer karena kesalahpahaman masyarakat bahwa kandungan nicotine pada rokok shisha lebih rendah dibandingkan rokok sigaret dan air yang digunakan bekerja sebagai filter, menghilangkan seluruh bahan kimia berbahaya seperti CO, nicotine dan tar. Selain itu terdapat beberapa mitos yang ada di masyarakat tentang merokok shisha antara lain shisha terdiri dari guci air yang dapat mengikat racun, lebih sedikit mengiritasi, sari buah yang ditambahkan pada shisha baik untuk kesehatan dan meninggalkan aroma yang menyenangkan.…”
unclassified
“…Penelitian lainnya yang dilakukan oleh Monna Hassan dan Ahmed Hassan di Arab Saudi mengenai efek dari tembakau terhadap kesehatan rongga mulut dimana dari 100% sampel, terdapat 38,1% pengguna shisha dan hasilnya menyatakan bahwa ada dampak buruk terhadap mukosa mulut seperti keratosis, hairy tongue, smoker's melanosis, stomatitis nikotina, dan lainnya. 3,6 Tinjauan literatur ini bertujuan untuk memberikan informasi terkait seberapa besar pengaruh buruk penggunaan rokok shisha bagi kesehatan rongga mulut yang diharapkan dapat berdampak pada penurunan prevalensi penggunaan rokok, khususnya shisha dan penyakit pada rongga mulut di Indonesia.…”
unclassified
See 1 more Smart Citation